The Association between Plasma 25OHD(3) Concentrations, C-Reactive Protein Levels, and Coronary Artery Atherosclerosis in Postmenopausal Monkeys - Schnatz, Peter F. (2012)
OBJECTIVE: To identify potential relationships between plasma 25OHD, C-reactive protein (CRP), coronary artery atherosclerosis (CAA), and coronary artery remodeling in monkeys consuming atherogenic diets. METHODS: Female cynomolgus monkeys (n=74) were fed a casein-lactalbumin (C/L) based, moderately atherogenic diet for 12 months. They then consumed either a soy (n=35) or C/L (n=39) based diet for 32 months. CRP concentrations were then determined and monkeys underwent surgical menopause. Each diet group was then re-randomized to receive soy (n=36) or C/L (n=38). After 32 post-menopausal months, 25OHD, CRP, CAA, and coronary artery remodeling were determined. All monkeys received a women’s equivalent of 1,000 IU/day of 25OHD(3) and 1,200 mg/day of calcium, throughout the study. RESULTS: The pre and post-menopausal dietary protein sources had no effect on post-menopausal 25OHD(3) concentrations (p=0.6). Across treatment groups, there was a statistically significant inverse relationship between 25OHD(3) concentrations and CRP at necropsy (r=-0.35, p=0.003). A significant inverse correlation between 25OHD(3) concentration and the change in CRP, from pre-menopause to post-menopause, was observed (r=-0.32, p=0.007). The significant associations identified between plasma 25OHD(3) and CRP remained after controlling for postmenopausal diet. Those monkeys with a greater increase in CRP also had significantly more CAA and less ability to maintain normal lumens by remodeling. CONCLUSIONS: Higher plasma concentrations of 25OHD(3) were associated with lower CRP. Lower CRP was associated with less coronary atherosclerosis and improved coronary artery remodeling. These findings suggest that 25OHD(3) concentrations are associated with an anti-inflammatory state and may support an association between oral 25OHD(3) and cardioprotection.